Insights into treatment of patients with mycosis fungoides or Sézary syndrome using mogamulizumab - Francine Foss; Youn H. Kim; Julia Scarisbrick; Oleg Akilov; Robert Ristuccia; Karen Dwyer; Wende Wu; Martine Bagot (Journal of Dermatological Treatment)
Purpose Mogamulizumab demonstrated improved outcomes vs. vorinostat across a range of disease and patient characteristics in patients with mycosis fungoides or Sézary syndrome in the MAVORIC trial.Materials and methods This post-hoc analysis further examined MAVORIC data to assess factors associated with long-term response (ORR >12 months), time to next treatment (TTNT), and impact of concomitant steroid use, lymphopenia, and mogamulizumab-associated rash (MAR) on patient response.Results A higher proportion of patients achieved ORR lasting ≥4, 6, 8, or 12 months in the mogamulizumab vs. vorinostat arm. Long-term response was also observed in mogamulizumab-treated patients with more advanced disease (stage IVA1 [17/20], B2 blood involvement [18/20], and SS [14/20]). PFS was significantly longer (9.4 vs. 3.1 months; p < 0.0001) in mogamulizumab vs. vorinostat-treated patients taking concomitant steroids. Mogamulizumab-treated patients experienced longer TTNT vs. vorinostat. Lymphopenia and MAR were associated with response to mogamulizumab.Conclusions MAVORIC demonstrated greater efficacy with mogamulizumab vs. vorinostat in relapsed/refractory patients with CTCL, including those with more advanced disease. Concomitant steroid use improved ORR and PFS but did not impact vorinostat outcomes. Overall responses occurred more frequently in mogamulizumab-treated patients that developed lymphopenia than those that did not. A higher percentage of patients with MAR had an overall response than those without MAR.